Connexin26 is Present in Rat Cardiomyocytes and Rat Cardiomyocyte Extracellular Vesicles - Alessandra Falleni; Antonella Cecchettini; Margherita Bernardeschi; Stefania Moscato; Letizia Mattii (Current Overview on Disease and Health Vol. 7, 2023)
In this chapter, we describe the results obtained from our two, recently published studies which aimed to demonstrate the presence of Cx26 and its immunolocalization in rat cardiomyocytes, in differentiated (d)H9c2 cardiac rat cells and in extracellular vesicles from dH9c2 cell supernatant. Connexins (Cxs) are a family of membrane-spanning proteins, expressed in vertebrates and named according to their molecular weight. They are known to form gap junctions, membrane channels mediating cell-cell communication, which play an essential role in the propagation of electrical activity in the heart. Cx26 has been described in a number of tissues and its mutations are frequently associated with deafness and skin diseases. Only recently, Cx26 has been described in the heart, at level of vessels and cardiomyocytes, and its localization is scattered all over the cell at the level of different subcellular compartments aside from at the intercalated discs as is the case for the other cardiac Cxs. The functional characterization of Cx26 in cardiomyocytes remains poorly understood due to this recent discovery in the heart tissues. However, the peculiar localization at the level of extracellular vesicles suggested a specific role for cardiac Cx26 in inter-cellular communication in a gap junction independent manner.